Opioidergic System and Functional Architecture of Intrinsic Brain Activity: Implications for Psychiatric Disorders. (August 2020) - Rocchi, Giulio; Sterlini, Bruno; Tardito, Samuele; Inglese, Matilde; Corradi, Anna; Filaci, Gilberto; Amore, Mario; Magioncalda, Paola; Martino, Matteo
The opioidergic system and intrinsic brain activity, as organized in large-scale networks such as the salience network (SN), sensorimotor network (SMN), and default-mode network (DMN), play core roles in healthy behavior and psychiatric disorders. This work aimed to investigate how opioidergic signaling affects intrinsic brain activity in healthy individuals by reviewing relevant neuroanatomical, molecular, functional, and pharmacological magnetic resonance imaging studies in order to clarify their physiological links and changes in psychiatric disorders. The SN shows dense opioidergic innervations of subcortical structures and high expression levels of opioid receptors in subcortical-cortical areas, with enhanced or reduced activity with low or very high doses of opioids, respectively. The SMN shows high levels of opioid receptors in subcortical areas and functional disconnection caused by opioids. The DMN shows low levels of opioid receptors in cortical areas and inhibited or enhanced activity with low or high doses of opioids, respectively. Finally, we proposed a working model. Opioidergic signaling enhances SN and suppresses SMN (and DMN) activity, resulting in affective excitation with psychomotor inhibition; stronger increases in opioidergic signaling attenuate the SN and SMN while disinhibiting the DMN, dissociating affective and psychomotor functions from the internal states; the opposite occurs with a deficit of opioidergic signaling.